AGAMA DAN MAGI BAGI KYAI DAN JAWARA - TIHAMI, M.A. (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2011)
This article tries to discuss the function and the role of religion and magic for kyai ('ulama') and Jawara (local strongmen) in Pasanggrahan, Pabuaran, Serang Banten where this research was conducted. It also tries to describe the meaning and functions of religion and magic for Pasanggrahan society. In this village, kyai, who obtain legitimation from religion (Islam) by his authority to lead religious ceremonies and to interpret religious doctrines, gains many opportunities to play a role in magical sciences derived from the religion; indeed, to upgrade them. It happens because in Islam there are magical elements which are inseparable from religion. Therefore, jawara obtains magic from kyai to meet their practical needs. Based on this relationship, it shows that magic is functionally needed by both of leaders (kyai and jawara) functioned to maintain their leadership. Moreover, each leader needs the perpetuation of the relationship by maintaining solidarity of the society through performing magic. Hence, it seems that the leadership of kyai and jawara in Pasanggrahan is in the networks of religion and magic. Keywords: kyai,jawara, tradisional leadership, magic Banten